Cations and dications of heavier group 14 elements in low oxidation states - Swamy, V. S. V. S. N.; Pal, Shiv; Khan, Shabana; Sen, Sakya S. (Dalton Transactions, 2015)
Cations and dications of heavier group 14 elements in their low oxidation state have received widespread attention in recent years. The journey started with the isolation of a series of cations of the composition [(C5Me5)E:](+) [E = Si-Pb], followed by the more recent isolation of a Ge(II) dication encapsulated within a cryptand, a carbodiphosphorane stabilized [GeCl](+) monocation with a two coordinate Ge atom, Si(II) cations and dications stabilized by N-heterocyclic carbenes (NHCs), which highlights the ongoing growth and interest in the chemistry of tetrel(II) cations. This is presumably because the central atom (E) in these compounds contains two or three unoccupied valence orbitals as well as holds a lone pair of electrons. Such an electronic description represents ambiphilicity, which is of great interest for catalysis. The successful synthesis of divalent group 14 cations requires new synthetic strategies based on the sterically demanding neutral or monoanionic ligands, utilization of counter anions, and solvents with low nucleophilicity in order to minimize the degree of interactions with the cations. An alternative approach for the realization of divalent cations of group 14 elements is their coordination to the transition metals. This synthetic approach was successfully applied for the isolation of a range of transition metal coordinated divalent cations of group 14 elements. Apart from arousing academic interest some of these cations have found application as activators in the Ziegler-Natta polymerization of alkenes.

Strikingly diverse reactivity of structurally identical silylene and stannylene - Parvin, Nasrina; Dasgupta, Rajarshi; Pal, Shiv; Sen, Sakya S.; Khan, Shabana (Dalton Transactions, 2017)
The reactivity of structurally identical silylene and stannylene [PhC(NtBu)(2)EN(SiMe3)(2)] (E = Si (1) and Sn (2)) towards coinage metals has been explored. While 1 has the propensity to form an adduct with coinage metals (4 and 5), 2 undergoes a ligand exchange reaction with copper halides and silver triflate leading to PhC(NtBu) 2SnX (X = Br (6), Cl (7), and OSO2CF3 (8)) with concomitant formation of [M{N(SiMe3) (2)}] (M = Cu, Ag). However, with AgSbF6 both 1 and 2 led to ion pairs, 9(+) .SbF(6)(-)and 10(+) . SbF(6)(-)displaying weaker Ag center dot center dot center dot center dot F interactions in the latter.

Bis(silanetellurone) with C-H center dot center dot center dot Te Interaction - Ghosh, Moushakhi; Panwaria, Prakash; Tothadi, Srinu; Das, Aloke; Khan, Shabana (Inorganic Chemistry, 2020)
Herein, we report the synthesis of a series of bis(silanechalcogenones) [Ch = Te (2), S (3), or Se (4)] using an N-heterocyclic silylene-based SiCSi pincer ligand (1). 2 is the first example of a bis(silanetellurone) derivative. The bonding patterns of 2-4 were extensively studied by natural bond orbital, quantum theory of atoms in molecules, and noncovalent interaction index analyses, and these exhibit weak C-H center dot center dot center dot Ch interaction. The analogous reaction of 1 with trimethyl N-oxide produced a novel bis(cyclosiloxane) derivative (5). All of the complexes are duly characterized by single-crystal X-ray diffraction studies, multinuclear nuclear magnetic resonance (H-1, C-13, and Si-29) spectroscopy, and high-resolution mass spectrometry.

Carbazole substituted amidinato silylene: synthesis, bonding, and coordination behavior with coinage metals - Ghosh, Moushakhi; Tothadi, Srinu; Khan, Shabana (Organometallics, 2021)
In this work, the synthesis and characterization of a new carbazole substituted amidinatosilylene (1) and its coinage metal complexes 3-8 are being reported. Before the complexation reactions, we prepared [PhC(N+Bu)(2)Si(Cbz)-> Co(CO)Cp] complex (2) to estimate the sigma-donating strength of the newly synthesized silylene 1. Further, several commonly available coinage metal salts were utilized for the complexation reactions with 1, which afforded complexes 3-8. The solid-state structures of 1-8 have been validated by single-crystal X-ray diffraction studies, NMR spectroscopy, and mass spectroscopy. DFT studies were also performed to understand the bonding scenario of 1 and 3-7. Of note, 1 consists of a HOMO on its carbazolide moiety, and the HOMO-1 features the silylene character. We also compared the HOMO-LUMO gap of 1 with other amidinato silylenes having different N-substitutions.

Diverse reactivity of NOBF4 towards silylene, disilene, germylene and stannylene - Parvin, Nasrina; Sen, Nilanjana; Muhasina, Puthan Veetil; Tothadi, Srinu; Parameswaran, Pattiyil; Khan, Shabana (Chemical Communications, 2021)
{The reactivity of NOBF4 towards silylene, disilene, germylene, stannylenes has been described. Smooth syntheses of compounds of composition [PhC(NtBu)(2)E(= O -> BF3)N(SiMe3)(2)

Reactivity of (TMS)(2)N(eta(1)-Cp*)Si=Si(eta(1)-Cp*)N(TMS)(2) toward the Halides of Groups 13-15 - Sen, Nilanjana; Parvin, Nasrina; Tothadi, Srinu; Khan, Shabana (Organometallics, 2021)
In this paper, we have demonstrated the unique reactivity of a previously reported disilene [(TMS)(2)N(eta(1)-Me5C5)Si=Si(eta(1)-Me5C5)N(TMS)(2)] (1) with the halides of groups 13-15, which resulted in the formation of silicon-E (E = B, Al, Ge, P) bonds. Treatment of 1 with Lewis acidic BCl3 led to the formation of a cationic boron species [Cp*BSi(Cl)(2)N(TMS)(2))][BCl3SiCl3] (2). In contrast, the reaction of 1 with BCy2Cl afforded an oxidative addition product [(TMS)(2)N(eta(1)-Me5C5)Si(BCy2)(Cl)] (3) via the insertion of a Si(II) atom into the B-Cl bond. Extending the reaction with its higher congener led to classical Lewis acid-base adducts, (TMS)(2)N(eta(1)-Me5C5)Si -> AlCl3 (4) and (TMS)(2)N(eta(1)-Me5C5)Si -> AlBr3 (5), respectively. The reaction of GeCl2 with 1 proceeded in a completely different manner and resulted in a hybrid dendrimeric compound [HGe(Si(Cl)(2)N(TMS)(2))(3)] (6), whereas, with SnCl2, it led to Cp*SnCl (7). Lastly, the reaction of Ph2PCl followed the same pattern like Cy2BCl and led to the formation of an oxidative addition product [(TMS)(2)N(eta(1)-Me5C5)Si(PPh2)(Cl)] (9) with a Si-P bond.

Synthesis and application of silylene-stabilized low-coordinate Ag(I)-arene cationic complexes - Parvin, Nasrina; Sen, Nilanjana; Tothadi, Srinu; Muhammed, Shahila; Parameswaran, Pattiyil; Khan, Shabana (Organometallics, 2021)
We report the first examples of N-heterocyclic silylene-stabilized monocoordinate Ag(I) cationic complexes weakly bound to the free arene rings (C6H6, C6Me6, and C7H8). Further, the application of these electrophilic Ag(I) complexes as catalysts has been investigated toward A(3)-coupling reactions, which afforded a series of propargylamines in good to excellent yields with low catalyst loading under a solvent-free condition (19 examples).

First-row transition metal complexes of a phosphine-silylene- based hybrid ligand - Akhtar, Ruksana; Kaulage, Sandeep H.; Sangole, Mayur P.; Tothadi, Srinu; Parvathy, Parameswaran; Parameswaran, Pattiyil; Singh, Kirandeep; Khan, Shabana (Inorganic Chemistry, 2022)
We have prepared two new silylene-phosphine-based hybrid ligands Si{N(R)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)} [R = TMS {trimethylsilyl} (1) and TBDMS {tert-butyldimethylsilyl} (2)], which possess two donor sites. Furthermore, the treatment of the bidentate ligand 1 with base metal halides {FeBr2, CoBr2, NiCl(2)middotdme [nickel chloride(II) ethylene glycol dimethyl ether]} and 2 with NiBr(2)middotdme [nickel bromide(II) ethylene glycol dimethyl ether] afforded four-coordinate six-membered metal complexes 3-6, respectively, which feature coordination from both Si(II) and P(III) sites. Subsequently, complexes 3 [(FeBr2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], 4 [(CoBr2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], 5 [(NiCl2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], and 6 [(NiBr2)Si{N((SiBuMe2)-Bu-t)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}] are studied for their redox and magnetic properties with the help of UV-vis spectroscopy, cyclic voltammetry, SQUID magnetometry, and theoretical calculations. Complexes 3-6 were found to display a paramagnetic behavior. All the compounds are well established by single-crystal X-ray diffraction studies.

Hybrid silylene-Pd catalyst: efficient C-N cross-coupling of sterically bulky amines and chiral amines - Kaulage, Sandeep H.; Parvin, Nasrina; Khopade, Kishor V.; Khan, Shabana (Chemical Communications, 2024)
Herein, we report a catalytic system with N-heterocyclic silylene (NHSi)-phosphine-based hybrid bidentate ligands [PhC(NtBu)2SiN(PR2)(2,6-iPr2-C6H3)] and Pd(dba)2, which serves as an effective catalyst for C-N cross-coupling of a wide range of sterically bulky amines and optically active amines, which is challenging otherwise. Herein, we report a hybrid silylene-based bidentate ligand (SiNP)-Pd(0) catalytic system, which performs the C-N coupling of difficult substrates, e.g., sterically bulky amines and chiral amines.

Ce[N(SiMe3)2]3(THF)3-catal yzed hydroboration of CO2, esters and epoxides with pinacolborane: selective synthesis of methanol in multigram scale - Hossain, Md Jabed; Shah, Brij Kumar; Dash, Soumya Ranjan; Vanka, Kumar; Khan, Shabana (Chemistry-A European Journal, 2025)
In this work, we have reduced CO2 with HBpin to afford borylated methanol product selectively in similar to 99 % yield using Ce[N(SiMe3)(2)](3)(THF)(3) as a catalyst. This led to multigram scale isolation of methanol obtained from CO2 reduction via the hydrolysis of borylated methanol, this establishes the potential of Ce[N(SiMe3)(2)](3)(THF)(3) as an efficient homogeneous catalyst for the bulk scale methanol synthesis. A practical application of this catalytic system was also shown by reducing CO2-containing motorbike exhaust efficiently and selectively. Further, C-O bond activation of esters and epoxides using HBpin and 1-2 mol % of Ce[N(SiMe3)(2)](3)(THF)(3) at 60 degrees C afforded the borylated alcohols in good to excellent yields, which can easily be hydrolysed to the eco-friendly corresponding alcohol. The stoichiometric experiments were performed to prove the formation of in-situ generated cerium hydride [Ce]-H as an active catalyst.
Keywords: Cerium; CO2 reduction; Epoxide; Ester; Hydroboration; Lanthanides

Silylene-copper(i) catalysis: regioselective protoboration of terminal alkynes - Kaulage, Sandeep H.; Shah, Brij Kumar; Panday, Rishukumar; Sharma, Himanshu; Vanka, Kumar; Khan, Shabana (Chemical Communications, 2025)
Herein, we report an efficient regioselective protoboration of the terminal alkynes catalyzed by newly synthesized silylene-copper(i)-aryl complexes. This method offers a broad substrate scope, good functional-group compatibility, and a gram-scale synthetic ability. The insight into the mechanistic cycle is also provided with the support of experimental and theoretical studies.

Harnessing strong chiroptical nonlinearity in carbene-copper-amides through center-specific chirality: an approach to amplified dissymmetry - Ghosh, Moushakhi; Tanwar, Riteeka; Panwaria, Prakash; Chatterjee, Abhijit; Panday, Rishukumar; Akhtar, Ruksana; Venugopal, Geethu; Mandal, Pankaj; Khan, Shabana (Journal of the American Chemical Society, 2026)
We present the design, synthesis, and photophysical characterization of a new class of chiral N-heterocyclic carbene (NHC)-copper(I)-amide (CMA) complexes with enantiomerically pure phenylethylamine motifs within the amide framework. These chiral CMA complexes represent a new class of mononuclear molecular Cu(I) complexes exhibiting pronounced chiral nonlinear optical (NLO) activity, which are actively being researched for advanced optoelectronic applications such as advanced photonics, biosensing, and security. The intrinsic molecular chirality and noncentrosymmetric crystal packing collectively enable strong second-harmonic generation (SHG) responses in the presence of circularly polarized (CP) light. Notably, these complexes display impressive SHG circular dichroism factors (g SHG-CD) as high as +/- 0.40 at 1000 nm, equaling or surpassing state-of-the-art chiral perovskites in this domain. Beyond their exceptional NLO response, the complexes exhibit dual emissive behavior, originating from both singlet and triplet excited states, with absolute quantum yields reaching 30%, and validated by TD-DFT calculations. The air-sensitive phosphorescence (similar to 550 nm) efficiently generates singlet oxygen (1O2), confirmed by PPh3 photooxidation and TEMPO radical generation. Remarkably, the emission can be reversibly switched between pure singlet and mixed singlet-triplet states by external modulation of O2, maintaining photostability over multiple oxic-anoxic cycles up to 5 days. These findings establish chiral CMA complexes as a new class of NHC-ligated molecular Cu(I) systems to display circularly polarized NLO activity with reversible photoluminescent switching, opening new avenues for exploring main-group organometallic compounds in next-generation polarization-sensitive photonic devices.